Les dispositifs pour collégiens à haut potentiel intellectuel en France : une analyse des besoins des élèves perçus par les chefs d’établissement - Karine Buard; Minna Puustinen; Amélie Courtinat-Camps (Recherches en Éducation)
Some French public middle schools offer gifted students the opportunity to pursue their education in general classes, while benefiting from specific facilities within the framework of a dedicated educational program. In this study, we sought to identify and analyze the needs of these pupils as perceived by the headmaster of each middle school in-volved. The results highlight two main student needs, common to all these programs (uneasiness and difficul-ties in peer relationships) but also needs specifically mentioned by some headmasters (for example, non-adaptive behavior).